2021
DOI: 10.3389/fpsyg.2021.544129
|View full text |Cite
|
Sign up to set email alerts
|

More Light? Opportunities and Pitfalls in Digitalized Psychotherapy Process Research

Abstract: While the evidence on the effectiveness of different psychotherapies is often strong, it is not settled whereby and how these therapies work. Knowledge on the causal factors and change mechanisms is of high clinical and public relevance, as it contributes to the empirically informed advancement of psychotherapeutic interventions. Here, digitalized research approaches might possess the potential to generate new insights into human behavior change, contributing to augmented interventions and mental healthcare pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Cognitive variables were found to be the most often investigated mediators, followed by a broad range of other mediators. Even though our eligibility criteria were not limited to a specific mental health condition in youth, only a rather low number of studies were identified by our systematic literature searches, a finding that corresponds to the limited evidence base of research on mechanisms of change in psychotherapy in general [ 37 , 74 ], and for children and adolescents in specific [ 24 , 35 , 37 ], necessitating further high-quality research efforts to improve interventions and mental health care practices for this younger age group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cognitive variables were found to be the most often investigated mediators, followed by a broad range of other mediators. Even though our eligibility criteria were not limited to a specific mental health condition in youth, only a rather low number of studies were identified by our systematic literature searches, a finding that corresponds to the limited evidence base of research on mechanisms of change in psychotherapy in general [ 37 , 74 ], and for children and adolescents in specific [ 24 , 35 , 37 ], necessitating further high-quality research efforts to improve interventions and mental health care practices for this younger age group.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the therapeutic or working alliance (ie, the professional relationship between therapists and patients; eg, Grawe et al [ 90 ]) was not evaluated as a mediator in any of the included studies. However, the recent development of the working alliance inventory for digital interventions [ 91 ] may contribute to future process research, informing the evidence base of the effects of a digital therapeutic alliance in DHIs for youth [ 37 , 92 ]. Furthermore, mediators that have not been investigated so far, such as behavioral and biological variables, should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This concern is also nourished by the massive commercialization of the app market and limited resources in healthcare globally, raising further methodological and ethical questions [ 59 , 60 ]. Thus, the adherence to well-established standards of good clinical practices as well as scientific-based intervention evaluation should be urgently applied for MHA [ 61 ], similar as it is largely the case for internet-based interventions and conventional psychotherapies offered face-to-face. Recommendations for quality criteria and standards for MHA are available, and can complement efficacy-/effectiveness studies on MHA in RCTs [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%